Surviving disruption: the grocer's tale. Issue 1 (11th November 2019) - Blitz, Amy
Abstract : Purpose: The US economy has undergone major macro disruption since the mid-1990s. Focusing on the retail grocery sector, this paper aims to compare the divergent strategies and outcomes of three key players to identify strategies that work vs those that do not during turbulent times, relevant to other sectors as well. Design/methodology/approach: Using the S&P 500 from 1996 to 2019 as a case selection method, the paper compares A&P, which died in 2015, one of just 12 of the original 500 companies to do so during the period; Kroger, which has held strong and has stayed on the S&P 500 list throughout the period; and Whole Foods, the only grocer to rise onto the list during the period, dropped in 2017 when it was bought by Amazon. Findings: A key differentiator separating A&P from Kroger and Whole Foods is relentless pursuit of customer satisfaction. This may seem axiomatic but is too often lost under investor pressures for short-term gains. Practical implications: Successful companies view such pursuit as an ongoing process requiring continual evolution even reinvention as customers' preferences and expectations change. Related to this is the need to maintain an ongoing focus on creating value for customers, as well as for the employees, suppliers and other key stakeholders who shape the customer experience. Finally, to maintain such a focus, companies must also commit to long-term investment not just short-term profits or gains for shareholders. Originality/value: The use of the S&P data as a case selection method frames the cases in context of the broader US economy and provides a strong foundation for comparing companies with diverse strategies and outcomes while facing the same macro disruptions and uncertainties.